Upaya Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Mekanika Teknik melalui Penerapan Model Pembelajaran GroupInvestigation (GI) Siswa Kelas X Teknik Bangunan SMK Negeri 2 Baubau Tahun Pelajaran 2018/2019 - Neneng Asniar Salihi (Jurnal Akademik FKIP Unidayan, 2020)
The purpose of this research was to (1) improve the increase of students learning achievement Group Investigation (GI) learning model in mechanic technique subject at grade X.2 Machine Technique of SMK Negeri 2 Baubau, (2) improve the increase of students activeness Group Investigation (GI) learning model in mechanic technique subject at grade X.2 Machine Technique of SMK Negeri 2 Baubau. This is Classroom Action Research (CAR) was conducted in two cycles. The technique of data analysis used was qualitative analysis. The results of the research showed that: (1) The implementation of Group Investigation (GI) learning model can improve students learning achievement. The improvement of students learning achievement can be seen from the percentage learning result by cognitive, affective, and psychomotor. The percentage of pre-cycle cognitive learning result was 68,75%, the first cycle was 78,12% and second cycle was 93,75%. Affective learning result pre-cycle was 53%, the first cycle was 66 % and the second cycle was 87%. Psychomotor learning result pre-cycle was 56%, the first cycle was 75 % and the second cycle was 87%. (2) The implementation of Group Investigation (GI) learning model can improve students activeness. Improve of students activeness can be seen from the increase of students activity. The based on these result was the implementation of Group Investigation (GI) learning model can improve achievement and activeness at grade X.2 Machine Technique of SMK Negeri 2 Baubau in mechanic technique subject.